A firm, bluish, hemorrhagic nodule on the left heel. (24th January 2013) - Kim, Hee Joo; Kim, Jong Yeob; Choi, Jae Eun; Kye, Young Chul; Ahn, Hyo Hyun; Seo, Soo Hong
Abstract : What is your diagnosis?